Therapeutic Effects of Oral Application of Menthol and Extracts from Tormentil (Potentilla erecta), Raspberry Leaves (Rubus idaeus), and Loosestrife (Lythrum salicaria) during Acute Murine Campylobacteriosis - Rasmus Bandick; Lia V. Busmann; Soraya Mousavi; Nizar W. Shayya; Jakub P. Piwowarski; Sebastian Granica; Matthias F. Melzig; Stefan Bereswill; Markus M. Heimesaat (MDPI AG, 2023)
Human food-borne infections with the enteropathogen Campylobacter jejuni are becoming increasingly prevalent worldwide. Since antibiotics are usually not indicated in campylobacteriosis, alternative treatment regimens are important. We here investigated potential disease-alleviating effects of menthol and of extracts from tormentil, raspberry leaves, and loosestrife in acute murine campylobacteriosis. Therefore, C. jejuni-infected microbiota-depleted IL-10−/− mice were orally treated with the compounds alone or all in combination from day 2 until day 6 post-infection. Whereas neither treatment regimen affected gastrointestinal pathogen loads, the combination of compounds alleviated C. jejuni-induced diarrheal symptoms in diseased mice on day 6 post-infection. Furthermore, the therapeutic application of tormentil and menthol alone and the combination of the four compounds resulted in lower colonic T cell numbers in infected mice when compared to placebo counterparts. Notably, pro-inflammatory cytokines measured in mesenteric lymph nodes taken from C. jejuni-infected mice following tormentil, menthol, and combination treatment did not differ from basal concentrations. However, neither treatment regimen could dampen extra-intestinal immune responses, including systemic pro-inflammatory cytokine secretion on day 6 post-infection. In conclusion, the combination of menthol and of extracts from tormentil, raspberry leaves, and loosestrife constitutes an antibiotic-independent approach to alleviate campylobacteriosis symptoms.